Mast cells in early rheumatoid arthritis associate with disease severity and support B cell autoantibody production. Issue 12 (20th August 2018) - Rivellese, Felice; Mauro, Daniele; Nerviani, Alessandra; Pagani, Sara; Fossati-Jimack, Liliane; Messemaker, Tobias; Kurreeman, Fina A S; Toes, René E M; Ramming, Andreas; Rauber, Simon; Schett, Georg; Jones, Gareth W; et al.
Abstract : Objectives: Mast cells (MCs) are involved in the pathogenesis of rheumatoid arthritis (RA). However, their contribution remains controversial. To establish their role in RA, we analysed their presence in the synovium of treatment-naïve patients with early RA and their association and functional relationship with histological features of synovitis. Methods: Synovial tissue was obtained by ultrasound-guided biopsy from treatment-naïve patients with early RA (n=99). Immune cells (CD3/CD20/CD138/CD68) and their relationship with CD117 + MCs in synovial tissue were analysed by immunohistochemistry (IHC) and immunofluorescence (IF). The functional involvement of MCs in ectopic lymphoid structures (ELS) was investigated in vitro, by coculturing MCs with naïve B cells and anticitrullinated protein antibodies (ACPA)-producing B cell clones, and in vivo in interleukin-27 receptor alpha (IL27 ra )-deficient and control mice during antigen-induced arthritis (AIA). Results: High synovial MC counts are associated with local and systemic inflammation, autoantibody positivity and high disease activity. IHC/IF showed that MCs reside at the outer border of lymphoid aggregates. Furthermore, human MCs promote the activation and differentiation of naïve B cells and induce the production of ACPA, mainly via contact-dependent interactions. In AIA, synovial MC numbers increase in IL27 ra deficient mice, in association with ELS and worse disease activity. Conclusions: Synovial MCs identify early RA patients with a severe clinical form of synovitis characterised by the presence of ELS.